Faktor Pemicu Terjadinya Selisih Anggaran dengan Pendapatan dan Belanja Daerah Pemerintah Kota Samarinda - Zahra Dewi Yuningtias; Delfia Uli Damayanti Siagian; Merina Tinta Fattrisia; Naili Sofia; Devia Amalia (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the financial performance of the Samarinda City Government from 2020 to 2022, including revenue variance, revenue growth, revenue effectiveness, and expenditure performance based on expenditure variance, expenditure growth, operational expenditure, capital expenditure, and expenditure efficiency. The financial ratios used include revenue variance, revenue growth rate, independence ratio, diversification degree, PAD effectiveness, expenditure variance, expenditure growth rate, operational cost ratio to total costs, capital expenditure ratio to total expenditure, and expenditure efficiency. The data used in this research is secondary data collected through documented library studies. The findings indicate that (1) the financial performance of Samarinda City's original revenue is generally quite good, with an average variance of 2.49% and a growth rate of 77.99%, while (2) expenditure growth shows a negative trend with an average of -0.027%.